The crown-of-thorns starfish genome as a guide for biocontrol of this coral reef pest - Hall, Michael R.; Kocot, Kevin M.; Baughman, Kenneth W.; Fernandez-Valverde, Selene L.; Gauthier, Marie E. A.; Hatleberg, William L.; Krishnan, Arunkumar; McDougall, Carmel; Motti, Cherie A.; Shoguchi, Eiichi; Wang, Tianfang; Xiang, Xueyan; et al. (Nature (London), 2017)
Genome sequencing and proteomic analyses of the crown-of-thorns starfish identify species-specific secreted factors that are associated with aggregating starfish and might be useful for biocontrol strategies. Sequencing a crown of thorns Crown-of-thorns starfish (COTS) are a predator of reef-building corals throughout the Indo-Pacific, where population outbreaks have led to loss of coral cover and biodiversity. Bernie Degnan and colleagues now report sequencing of the genomes of two COTS, Acanthaster planci , from the Great Barrier Reef in Australia and the reefs of Okinawa, Japan. They also sequenced transcriptomes from several external tissues and organs, and examined secreted proteins released into the water by aggregated or alarmed COTS. The genomic insights provided by this study may help to guide development of targeted treatments for reef-threatening outbreaks of the predatory starfish. The crown-of-thorns starfish (COTS, the Acanthaster planci species group) is a highly fecund predator of reef-building corals throughout the Indo-Pacific region 1 . COTS population outbreaks cause substantial loss of coral cover, diminishing the integrity and resilience of reef ecosystems 2 , 3 , 4 , 5 , 6 . Here we sequenced genomes of COTS from the Great Barrier Reef, Australia and Okinawa, Japan to identify gene products that underlie species-specific communication and could potentially be used in biocontrol strategies. We focused on water-borne chemical plumes released from aggregating COTS, which make the normally sedentary starfish become highly active. Peptide sequences detected in these plumes by mass spectrometry are encoded in the COTS genome and expressed in external tissues. The exoproteome released by aggregating COTS consists largely of signalling factors and hydrolytic enzymes, and includes an expanded and rapidly evolving set of starfish-specific ependymin-related proteins. These secreted proteins may be detected by members of a large family of olfactory-receptor-like G-protein-coupled receptors that are expressed externally, sometimes in a sex-specific manner. This study provides insights into COTS-specific communication that may guide the generation of peptide mimetics for use on reefs with COTS outbreaks.